Design of a Maximally Permissive Liveness-enforcing Supervisor with Reduced Complexity for Automated Manufacturing Systems - Wang, ShouGuang; Zhou, MengChu; Wu, WenHui (Asian journal of control, 2015)
This paper deals with the problems of computational and structural complexity in designing maximally permissive liveness‐enforcing supervisors for a class of Petri nets called Systems of Simple Sequential Processes with Resources (S3PR) without ξ‐resources. The supervisor consists of two parts: the first part proposes an algorithm to extract a desired emptied strict minimal siphon (SMS) from a given emptied siphon based on loop resource subsets. This is faster than the existing ones. The second part proposes a siphon‐based deadlock prevention policy, which can obtain a maximally permissive liveness‐enforcing supervisor with reduced structural complexity and no weighted monitors, owing to the contribution of the first part, which can compute a desired SMS such that one with the smallest number of resource places is selected first for control. Several flexible manufacturing systems are used to show the proposed method and its superior performance over the previous ones.